2018
DOI: 10.1111/cns.12793
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of peripheral blood immune cell populations in multiple sclerosis patients before and during treatment with a sphingosine‐1‐phosphate receptor modulator

Abstract: Our study corroborates changes in the composition of circulating immune cells in response to fingolimod and delineates the respective implications at the RNA level. Our data may be valuable for comparing the effects of novel S1P receptor modulating agents, which may be a therapeutic option for patients with secondary progressive MS as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…The discrepancy may be related to the clinical population, as we examined SPMS participants. As expected, genes related to the mechanism of action of an S1PR modulator, such as S1PR1 and CCR7, were downregulated, as reported with fingolimod (13,14). Furthermore, we found that siponimod exerted an antiinflammatory effect through the downregulation of AKT3, CD19, CD40, CD40L, IL23A, CXCR5, IL2RA, IL7R, IL23A, IL21R, IL11RA, IL6ST, CR2, and IRF4 genes, which is similar to what has been observed in RRMS patients treated with fingolimod (15).…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 78%
“…The discrepancy may be related to the clinical population, as we examined SPMS participants. As expected, genes related to the mechanism of action of an S1PR modulator, such as S1PR1 and CCR7, were downregulated, as reported with fingolimod (13,14). Furthermore, we found that siponimod exerted an antiinflammatory effect through the downregulation of AKT3, CD19, CD40, CD40L, IL23A, CXCR5, IL2RA, IL7R, IL23A, IL21R, IL11RA, IL6ST, CR2, and IRF4 genes, which is similar to what has been observed in RRMS patients treated with fingolimod (15).…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 78%
“…Clinical heterogeneous response to different treatments exists in MS patients, possibly partially due to the heterogeneity of MS pathology. This is why an exhaustive analysis of the immunological background of the patients and knowledge on their ability to respond to different therapeutic alternatives is still needed . We examined in the present study changes in leukocyte subpopulations and their association with clinical and brain MRI activity in RRMS patients before and during 1 year of follow‐up under fingolimod treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed an independent validation of our approach using a “validation dataset” (see methods) including adipocytes, progenitor cells (CD45 - CD34 + CD31 - ) and monocytes/macrophages (CD45 + CD14 + ) directly isolated from adipose tissue across 19 individuals (10 control and 9 obese) [10] and B cells, CD4 + T cells, CD8 + T cells, natural killer cells, and monocytes directly isolated from blood [11]. We use this validation dataset to evaluate the gene expression deconvolution approach on isolated cell types and to test the specificity of the proposed primary markers identified by CellMaDe.…”
Section: Resultsmentioning
confidence: 99%